Regression Facial Attribute Classification via simultaneous dictionary learning. (February 2017) - Moeini, Ali; Moeini, Hossein; Safai, Armon Matthew; Faez, Karim
Abstract: Recently, many researchers have attempted to classify Facial Attributes (FAs) by representing characteristics of FAs such as attractiveness, age, smiling and so on. In this context, recent studies have demonstrated that visual FAs are a strong background for many applications such as face verification, face search and so on. However, Facial Attribute Classification (FAC) in a wide range of attributes based on the regression representation -predicting of FAs as real-valued labels- is still a significant challenge in computer vision and psychology. In this paper, a regression model formulation is proposed for FAC in a wide range of FAs (e.g. 73 FAs). The proposed method accommodates real-valued scores to the probability of what percentage of the given FAs is present in the input image. To this end, two simultaneous dictionary learning methods are proposed to learn the regression and identity feature dictionaries simultaneously. Accordingly, a multi-level feature extraction is proposed for FAC. Then, four regression classification methods are proposed using a regression model formulated based on dictionary learning, SRC and CRC. Convincing results are acquired to handle a wide range of FAs and represent the probability of FAs on the PubFig, LFW, Groups and 10k US Adult Faces databases compared to several state-of-the-art methods. Highlights: This paper proposes a method for regression facial attributes classification. We propose two simultaneous optimization problems for Facial Attribute Classification. A multilevel feature extraction method was proposed to discriminate the facial features. Promising results were obtained to classify facial attributes on the PubFig, Groups, 10k US adult and LFW databases.